PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KEPUASAN KERJA (Studi Pada Unit Pelayanan Pendapatan dan Pemberdayaan Aset Daerah Koordinator PATI) - Sofuan, Moh; Setyowati, Widhy (Jurnal Ilmiah Telaah Manajemen, 2014)
The purpose of this study was to examine and analyze the effect of Compensation and Working Environment Against Employee Performance With Mediation Job Satisfaction (Study on Unit Revenue Service and Empowerment of Regional Asset Coordinator PATI). The method used in this research using census method by using the entire amount of the population that is 102 respondents. Testing of this study consisted of descriptive statistics, test instrument (validity test KMO> 0.5 and Loading Factor> 0.4 and reliability tests with Cronbach alpha> 0.7), the test model (Test Adj R2 (coefficient of determination) and Test F (Goodness of Fit) with level sig <0.05), test hypotheses using regression analysis with level sig <0.05 and test the mediating effect by using path analysis. The results of this study are: Compensation has a positive and significant impact on job satisfaction, work environment has a positive and significant impact on job satisfaction, job satisfaction has a positive and significant impact on performance, compensation has a positive and significant impact on the performance without the mediation of job satisfaction , the working environment has a significant positive effect on the performance of the mediation job satisfaction. Keywords: compensation, work environment, job satisfaction and performance.